A Hospital-based Case-control Study of Diarrhea in Children in Shanghai. Issue 11 (November 2017) - Chang, Hailing; Zhang, Ling; Ge, Yanling; Cai, Jiehao; Wang, Xiangshi; Huang, Zheng; Guo, Jiayin; Xu, Hao; Gu, Zhen; Chen, Hong; Xu, Xuebin; Zeng, Mei
Abstract : Background: Prevention and control of childhood diarrhea is a global priority. We conducted a case-control study of childhood diarrhea in Shanghai. Methods: We prospectively recruited diarrheal children in an outpatient setting. Nondiarrheal controls were individually matched to cases. Rotavirus, norovirus and bacterial pathogens were examined. Clinical and epidemiologic data were obtained at enrollment and follow-up. Results: Potential pathogens identified in 680 diarrheal cases and 680 controls were rotavirus (19.0% vs. 1.3%), norovirus (13.4% vs. 4.7%), nontyphoidal Salmonella (9.3% vs. 1.9%), enteropathogenic Escherichia coli (8.4% vs. 6.9%) and enteroaggregative Escherichia coli (7.2% vs. 6.2%) and Campylobacter (5.1% vs. 1.2%), enterotoxigenic Escherichia coli (1.2% vs. 0.6%), enterohemorrhagic Escherichia coli (0.3% vs. 0%) and Shigella (0.15% vs. 0%), respectively. The specificity and sensitivity of fecal leukocytes >5 per high-power field for the diagnosis of bacterial diarrhea were 94.2% and 22.8%. Salmonella were susceptible to ciprofloxacin, ceftriaxone and amoxicillin-clavulanate and showed low frequency of resistance to azithromycin. Campylobacter showed low frequency of resistance to azithromycin and high frequency of resistance to ciprofloxacin. Diarrheagenic Escherichia coli was highly susceptible to ciprofloxacin and amoxicillin-clavulanate. Contact with diarrheal patients was a risk factor for rotavirus [adjusted odds ratio (aOR): 11.7], norovirus (aOR: 7.5) and Campylobacter (aOR: 27.1) infections. Mother's education was positively associated with Salmonella infection (aOR: 2.1). Good hand hygiene was protective against rotavirus (aOR: 0.6), norovirus (aOR: 0.5) and Salmonella (aOR: 0.3) infections. Conclusions: Rotavirus, norovirus, nontyphoidal Salmonella and Campylobacter are significantly associated with diarrhea in Chinese children. Fecal leukocytes >5 per high-power field can predict bacterial diarrhea. Target prevention and appropriate treatment of diarrhea should consider the potential pathogen and resistance pattern. Abstract : Supplemental Digital Content is available in the text.